Social rights: The new constitutional heritage and its issues - González Tugas, Juan Andrés (Derecho Público Iberoamericano, 2018)
The present text summarizes the different constitutional traditions to confront their postulates before the recognition of new rights, especially the irruption of social rights. Thus, the analysis describes the three classical traditions that seek to establish an effective system of limits and counterweights to power: the English, the American and the French. Then, the German constitutional tradition is exposed in what concerns the recognition of certain fundamental values to avoid the consequences of pure positivism of the rules and the excesses of authoritarianism. The text continues with the irruption of social rights as a new constitutional tradition and the experience of multilevel constitutionalism in the European Union. At the end of the work, a series of problems that raise the tradition of social rights are exposed.